NOH : - Nakamura, Yasuo (Walker/Weatherhill, 1971)
This book introduces Noh from the viewpoint of the intelligent amatuer who wishes to know the basic facts about it. the approach is largesly a visual one, as the generous selection of illustrations makes clear. Character types, masks, costumes, properties, drawings and paitings from Noh history all thse complement a text that traces the development of Noh, explains its techniques, interprets its aesthetic, and re-creates the atmosphere of the theater in which it is performed.